2021
DOI: 10.3389/fimmu.2020.626792
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast in Refractory Behçet’s Syndrome: A Multicenter Observational Study

Abstract: ObjectiveMucocutaneous and joint disorders are the most common manifestations in Behçet’s syndrome (BS) and are frequently clustered in the so-called minor forms of BS. There remains a need for safe and effective treatment for joint lesions in BS. We report the long-term safety and effectiveness of apremilast in refractory joint and mucocutaneous manifestations of BS.MethodsFrench nationwide multicenter study including 50 BS patients with either active joint and/or mucocutaneous manifestations resistant to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…The long‐term efficacy of apremilast has been reported for oral ulcers for up to 64 weeks 23 and for skin and articular symptoms for up to 6 months 22,24–26 . However, similar to the present report, there have been reports of only skin lesions or arthritis flare‐ups during apremilast treatment, 20,24 and the effect on oral ulcers may not match the effect on skin or arthritis.…”
Section: Discussionsupporting
confidence: 58%
“…The long‐term efficacy of apremilast has been reported for oral ulcers for up to 64 weeks 23 and for skin and articular symptoms for up to 6 months 22,24–26 . However, similar to the present report, there have been reports of only skin lesions or arthritis flare‐ups during apremilast treatment, 20,24 and the effect on oral ulcers may not match the effect on skin or arthritis.…”
Section: Discussionsupporting
confidence: 58%
“…Among 30 patients who had refractory joint involvement, 65% had complete response and 17% had partial response at month 6. 71 Apremilast was generally well tolerated, the main AEs being related to the gastrointestinal system.…”
Section: Small Molecules Apremilastmentioning
confidence: 97%
“…The first meta-analysis on the effectiveness of apremilast for involvement other than BD-associated OU by Iizuka et al showed that apremilast significantly improved GU, EN, pseudofolliculitis, and arthritis within 12 weeks from the initiation of administration (4). The meta-analysis included studies targeting patients with mucocutaneous and joint involvement who were resistant to colchicine, systemic glucocorticoids, and immunosuppressive agents (2,(5)(6)(7)(8)(9). Most of the studies included patients who were refractory to treatment with tumour necrosis factor (TNF) inhibitors (up to 76.9%), with different percentages in each study (5)(6)(7)(8)(9).…”
Section: Sirsmentioning
confidence: 99%
“…The meta-analysis included studies targeting patients with mucocutaneous and joint involvement who were resistant to colchicine, systemic glucocorticoids, and immunosuppressive agents (2,(5)(6)(7)(8)(9). Most of the studies included patients who were refractory to treatment with tumour necrosis factor (TNF) inhibitors (up to 76.9%), with different percentages in each study (5)(6)(7)(8)(9). Apremilast inhibits the production of TNF and other inflammatory cytokines and promotes the production of the anti-inflammatory cytokine interleukin-10 (1, 2, 9).…”
Section: Sirsmentioning
confidence: 99%